2018
DOI: 10.1111/tid.12953
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of invasive mold diseases in patients with hematological malignancies using Aspergillus, Mucorales, and panfungal PCR in BAL

Abstract: This study illustrates that the diagnosis of IMD is still very problematic and lacks objectivity. Together with GM in BAL, the PCRs may prove an addition to the current available diagnostic armamentarium in IMD because of their ability to identify molds on a species level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The second case (possible IFD) could not be confirmed on sequence level. Similar frequencies of Fusarium in BALF were recently described by two studies, ranging from 0.6 to 2% [20,21]. Because of this low frequency, clinical diagnostic studies regarding pulmonary fusariosis are difficult to perform, as huge patient numbers are necessary.…”
Section: Discussionsupporting
confidence: 67%
“…The second case (possible IFD) could not be confirmed on sequence level. Similar frequencies of Fusarium in BALF were recently described by two studies, ranging from 0.6 to 2% [20,21]. Because of this low frequency, clinical diagnostic studies regarding pulmonary fusariosis are difficult to perform, as huge patient numbers are necessary.…”
Section: Discussionsupporting
confidence: 67%
“…However, as only 10% of samples originated from patients with suspected IPA, patient-specific factors such as antifungal pretreatment, immune reconstitution, alloreactive inflammation, and impaired mucociliary clearance remain crucial in determining which child might develop IPA [16]. While this study was not powered to assess performance characteristics of this assay for IPA, pan-fungal and Aspergillus-specific PCR have demonstrated 76%-79% sensitivity and 93%-95% specificity for probable/proven IPA [14,[40][41][42][43][44][45][46][47]. Combining nucleic acid tests with galactomannan can hasten diagnosis and improve clinical outcomes in some populations [48][49][50][51]; further, incorporation of immune function may also improve discrimination of colonization and invasive mycosis [52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the interpretation of panfungal PCR results performed on non-sterile samples, particularly BALF, is more difficult (Halliday et al, 2015;Bezdicek et al, 2016;Rahn et al, 2016;Trubiano et al, 2016;Wehrle-Wieland et al, 2018). A positive result returned on BALF may indicate lung infection but also airway colonization or environmental contamination especially if non-pathogenic fungal species are detected.…”
Section: Panfungal Pcr Assaysmentioning
confidence: 99%
“…Sequencing the PCR product may also result in a mixed "signal" due to multiple fungal species being present (Bezdicek et al, 2016;Zeller et al, 2017); this can be partially overcome by post PCR high-resolution melt curve analysis rather than using sequencing (Bezdicek et al, 2016). The sensitivity of panfungal PCR on BALF is lower in patients receiving moldactive treatment (Trubiano et al, 2016;Wehrle-Wieland et al, 2018). While panfungal PCR on BALF has the potential to identify more fungal species than culture, a study by Bousbia et al (2012) reported more episodes of pneumonia were diagnosed by culture (42%) than by molecular methods (17%).…”
Section: Panfungal Pcr Assaysmentioning
confidence: 99%